Getting small to feel big: the psychology of weight cutting in combat sports - Levy, J. J.; Boyd, C. (Frontiers in Sports and Active Living, 2025)
This mini review explores the psychological factors associated with weight cutting practices among combat sport athletes. We overviewed combat sport athletes' extrinsic and intrinsic motivations for their sport participation and performance expectations and goals associated with weight cutting. Next, we reviewed the extant research on psychological risk factors associated with weight cutting with a particular focus on combat sport athletes' relationship with food, societal expectations concerning body image, and disordered eating. Finally, we examined how applying task-oriented strategies and Goal Attainment Theory aligns with combat sport athletes' motivation for sport participation. We called for further research into exploring how promoting gradual weight loss may promote psychological resilience with the goal of promoting healthier weight management strategies among combat sport athletes.